Interlayer film for laminated glass and laminated glass
The laminated glass interlayer film, composed of a thermoplastic resin and plasticizer, addresses the challenges of high-energy glass production by suppressing foaming and enhancing transparency under low-pressure conditions, thus offering a cost-effective and environmentally friendly solution.
Patent Information
- Application Number
- JP2020570993
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-09
- Filing Date
- 2020-12-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-12-03
AI Technical Summary
The production of laminated glass using high temperature and high pressure treatment in an autoclave is costly, energy-intensive, and can damage functional films, while conventional methods without autoclave treatment can lead to foaming at the edges and reduced transparency.
A laminated glass interlayer film with a single layer or multi-layer structure, including a first layer made of a thermoplastic resin and plasticizer, specifically designed to withstand compression creep tests without significant thickness change, thereby suppressing foaming and enhancing transparency.
The interlayer film allows for the production of laminated glass under low temperature and pressure conditions, reducing capital investment and carbon emissions, while maintaining or improving the transparency and penetration resistance of conventional laminated glass.
Smart Images

Figure 0007660378000004 
Figure 0007660378000005 
Figure 0007660378000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an interlayer film for laminated glass used to obtain laminated glass. The present invention also relates to laminated glass using the interlayer film for laminated glass. [Background technology]
[0002] Laminated glass is excellent in safety because even if it is broken by an external impact, the amount of glass fragments scattered is small. For this reason, the laminated glass is widely used in automobiles, railway vehicles, aircraft, ships, buildings, etc.
[0003] The above-mentioned laminated glass is generally produced by sandwiching an interlayer film for laminated glass between two glass plates, and then performing a high-temperature and high-pressure treatment in an autoclave to pressure-bond the interlayer film and the glass plates (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-190947 A Summary of the Invention [Problem to be solved by the invention]
[0005] The high-temperature and high-pressure treatment in an autoclave during the production of laminated glass is carried out under conditions of, for example, 130° C. or higher and 1 MPa or higher. However, the high-temperature and high-pressure treatment in an autoclave is a process that requires a large capital investment and also emits a large amount of carbon dioxide.
[0006] Furthermore, in an interlayer film having a functional film such as a light control film, the functional film may deteriorate when subjected to high-temperature and high-pressure treatment in an autoclave.
[0007] On the other hand, when laminated glass is produced using a conventional interlayer without performing high-temperature, high-pressure treatment in an autoclave, bubbles may form at the edges of the laminated glass and the transparency of the laminated glass may decrease.
[0008] An object of the present invention is to provide an interlayer film for laminated glass that can suppress the generation of bubbles at the edges of the laminated glass without high-temperature and high-pressure treatment in an autoclave and can increase the transparency of the laminated glass. Another object of the present invention is to provide laminated glass using the interlayer film for laminated glass. [Means for solving the problem]
[0009] According to a broad aspect of the present invention, there is provided an interlayer film for laminated glass having a single-layer structure or a structure of two or more layers, the interlayer film comprising a first layer, wherein when a test sample A having a diameter of 8 mm and a thickness of 0.8 mm obtained by cutting out the first layer is subjected to the following compressive creep test, the amount of change in thickness of test sample A before and after the compressive creep test is 50 μm or more and 325 μm or less (in this specification, "interlayer film for laminated glass" may be abbreviated to "interlayer film").
[0010] Compression creep test: With a load of 410 g applied to test sample A, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample A at 30°C immediately after holding it at 30°C for 5 minutes before starting the compression creep test and the thickness of test sample A immediately after holding it at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample A before and after the compression creep test.
[0011] According to a broad aspect of the present invention, there is provided an interlayer film for laminated glass having a one-layer structure or a two or more layer structure, the interlayer film comprising a first layer having a thickness of 200 μm or more and 900 μm or less, the thickness of the first layer being T B The diameter of the first layer is 8 mm and the thickness is T BWhen the following compression creep test is performed on test sample B having a thickness of 100 μm, the change in thickness of test sample B before and after the compression creep test is 50 μm or more and 325 μm or less (in this specification, "interlayer film for laminated glass" may be abbreviated to "interlayer film").
[0012] Compression creep test: With a load of 410 g applied to test sample B, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample B at 30°C immediately after holding it at 30°C for 30 minutes before starting the compression creep test and the thickness of test sample B immediately after holding it at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample B before and after the compression creep test.
[0013] According to a broad aspect of the present invention, there is provided an interlayer film for laminated glass having a one-layer structure or a two-layer or more structure, the interlayer film having a first layer and a thickness of 80 μm or more and 1600 μm or less, and the thickness of the interlayer film is T C μm, the diameter of the interlayer film is 8 mm and the thickness is T C When the following compression creep test is performed on test sample C having a thickness of 100 μm, the change in thickness of test sample C before and after the compression creep test is 50 μm or more and 325 μm or less (in this specification, "interlayer film for laminated glass" may be abbreviated to "interlayer film").
[0014] Compression creep test: With a load of 410 g applied to test sample C, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample C at 30°C at the start of the compression creep test and the thickness of test sample C immediately after being held at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample C before and after the compression creep test.
[0015] In a specific aspect of the interlayer film according to the present invention, the first layer contains a thermoplastic resin and a plasticizer.
[0016] In a specific aspect of the interlayer film according to the present invention, the thermoplastic resin contained in the first layer is a polyvinyl acetal resin.
[0017] In a specific aspect of the interlayer film according to the present invention, the interlayer film has a structure of two or more layers and further includes a second layer, the second layer being disposed on a first surface side of the first layer.
[0018] In a specific aspect of the interlayer film according to the present invention, the first layer is a surface layer in the interlayer film.
[0019] According to a broad aspect of the present invention, there is provided laminated glass comprising a first laminated glass component, a second laminated glass component, and the above-mentioned interlayer film for laminated glass, wherein the interlayer film for laminated glass is disposed between the first laminated glass component and the second laminated glass component. Effect of the Invention
[0020] The interlayer film according to the present invention has a one-layer structure or a two or more layer structure. The interlayer film according to the present invention has a first layer. When the above-mentioned compression creep test is performed on test sample A having a diameter of 8 mm and a thickness of 0.8 mm obtained by cutting out the first layer, the change in thickness of test sample A before and after the compression creep test is 50 μm or more and 325 μm or less. Since the interlayer film according to the present invention has the above configuration, it is possible to suppress the generation of bubbles at the edge of the laminated glass and to increase the transparency of the laminated glass without performing high-temperature and high-pressure treatment in an autoclave.
[0021] The interlayer film according to the present invention has a one-layer structure or a two-layer or more structure. The interlayer film according to the present invention has a first layer having a thickness of 200 μm or more and 900 μm or less. In the interlayer film according to the present invention, the thickness of the first layer is T B The diameter and thickness of the cut-out first layer are 8 mm and T BWhen the above-mentioned compression creep test was performed on test sample B having a thickness of 100 μm, the change in thickness of test sample B before and after the compression creep test was 50 μm or more and 325 μm or less. Since the interlayer film according to the present invention has the above-mentioned configuration, it is possible to suppress the generation of bubbles at the edges of the laminated glass and to increase the transparency of the laminated glass without the need for high-temperature and high-pressure treatment in an autoclave.
[0022] The interlayer film according to the present invention has a one-layer structure or a two-layer or more structure. The interlayer film according to the present invention has a first layer. The interlayer film according to the present invention has a thickness of 80 μm or more and 1600 μm or less. The interlayer film according to the present invention has a thickness of T C μm, the diameter of the interlayer film is 8 mm and the thickness is T C When the above-mentioned compression creep test was performed on test sample C having a thickness of 100 μm, the change in thickness of test sample C before and after the compression creep test was 50 μm or more and 325 μm or less. Since the interlayer film according to the present invention has the above-mentioned configuration, it is possible to suppress the generation of bubbles at the edges of the laminated glass and to increase the transparency of the laminated glass without the need for high-temperature and high-pressure treatment in an autoclave. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of an interlayer film for laminated glass according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of an interlayer film for laminated glass according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates an interlayer film for laminated glass according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view that illustrates an example of laminated glass using the interlayer film for laminated glass shown in FIG. [Diagram 5] 5(a) to (e) are examples of photographed images used to evaluate bubbles at the edge of laminated glass. [Figure 6]5(a) to (e) are examples of photographed images used to evaluate the transparency of laminated glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described in detail below.
[0025] (Interlayer film for laminated glass) The interlayer film for laminated glass according to the present invention (hereinafter sometimes abbreviated as "interlayer film") has a single layer structure or a two or more layer structure. The interlayer film according to the present invention has a first layer. When the following compression creep test is performed on test sample A obtained by cutting out the first layer and having a diameter of 8 mm and a thickness of 0.8 mm, the change in thickness of test sample A before and after the compression creep test is 50 μm or more and 325 μm or less.
[0026] Compression creep test: With a load of 410 g applied to test sample A, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample A at 30°C immediately after holding it at 30°C for 5 minutes before starting the compression creep test and the thickness of test sample A immediately after holding it at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample A before and after the compression creep test.
[0027] Specifically, a load of 410 g is applied to test sample A in an environment of 30° C., and the test sample A is held at 30° C. for 5 minutes with this load applied, and the thickness of test sample A at 30° C. immediately after holding at 30° C. for 5 minutes is measured. Also, a load of 410 g is applied to test sample A in an environment of 30° C., and the test sample A is held at 30° C. for 5 minutes with this load applied, and then the temperature is increased from 30° C. to 90° C. at a rate of 6° C. / min, and then held at 90° C. for 5 minutes, and the thickness of test sample A at 90° C. immediately after holding at 90° C. for 5 minutes is measured. A load of 410 g is applied to test sample A, and the thickness is measured with the load applied, until the thickness of test sample A at 90° C. immediately after holding at 90° C. for 5 minutes is measured.
[0028] The interlayer film for laminated glass according to the present invention (hereinafter sometimes abbreviated as "interlayer film") has a one-layer structure or a two-layer or more structure. The interlayer film according to the present invention has a first layer having a thickness of 200 μm or more and 900 μm or less. In the interlayer film according to the present invention, the thickness of the first layer is T B The diameter and thickness of the cut-out first layer are 8 mm and T B When the following compression creep test is performed on test sample B having a thickness of 1.0 μm, the change in thickness of test sample B before and after the compression creep test is 50 μm or more and 325 μm or less.
[0029] Compression creep test: With a load of 410 g applied to test sample B, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample B at 30°C immediately after holding it at 30°C for 30 minutes before starting the compression creep test and the thickness of test sample B immediately after holding it at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample B before and after the compression creep test.
[0030] Specifically, a load of 410 g is applied to test sample B in an environment of 30° C., and the test sample B is held at 30° C. for 30 minutes with this load applied, and the thickness of test sample B at 30° C. immediately after holding at 30° C. for 30 minutes is measured. Also, a load of 410 g is applied to test sample B in an environment of 30° C., and the test sample B is held at 30° C. for 30 minutes with this load applied, and then the temperature is increased from 30° C. to 90° C. at a rate of 6° C. / min, and then held at 90° C. for 5 minutes, and the thickness of test sample B at 90° C. immediately after holding at 90° C. for 5 minutes is measured. A load of 410 g is applied to test sample B, and the thickness is measured with the load applied, until the thickness of test sample B at 90° C. immediately after holding at 90° C. for 5 minutes is measured.
[0031] The interlayer film for laminated glass according to the present invention (hereinafter sometimes abbreviated as "interlayer film") has a one-layer structure or a two-layer or more structure. The interlayer film according to the present invention has a first layer. In the interlayer film according to the present invention, the thickness of the interlayer film is 80 μm or more and 1600 μm or less. In the interlayer film according to the present invention, the thickness of the interlayer film is TC μm, the diameter of the interlayer film is 8 mm and the thickness is T C When the following compression creep test is performed on test sample C having a thickness of 1.0 μm, the change in thickness of test sample C before and after the compression creep test is 50 μm or more and 325 μm or less.
[0032] Compression creep test: With a load of 410 g applied to test sample C, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the sample is held at 90°C for 5 minutes. The absolute value of the difference between the thickness of test sample C at 30°C at the start of the compression creep test and the thickness of test sample C immediately after being held at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of test sample C before and after the compression creep test.
[0033] Specifically, a load of 410 g is applied to test sample C in an environment of 30° C., and the thickness of test sample C at 30° C. immediately after the load is applied is measured. Also, a load of 410 g is applied to test sample C in an environment of 30° C., and while this load is applied, the temperature is raised from 30° C. to 90° C. at a rate of 6° C. / min immediately after the load is applied, and then the sample is held at 90° C. for 5 minutes, and the thickness of test sample C at 90° C. immediately after the 5 minutes of holding at 90° C. is measured. A load of 410 g is applied to test sample C until the thickness of test sample C at 90° C. immediately after the 5 minutes of holding at 90° C. is measured, and the thickness is measured with the load applied.
[0034] The interlayer film according to the present invention has the above-described configuration, and therefore can suppress the generation of bubbles at the edges of the laminated glass without the need for high-temperature, high-pressure treatment in an autoclave, and can increase the transparency of the laminated glass.
[0035] The interlayer film according to the present invention allows laminated glass to be produced under conditions of low temperature and low pressure (for example, 100°C or lower and 0.5 MPa or lower) compared to high temperature and high pressure treatment in an autoclave. Therefore, laminated glass can be produced without large capital investment in equipment such as an autoclave, and carbon dioxide emissions during laminated glass production can be reduced. Furthermore, the production capacity of conventional laminated glass production methods that involve autoclave treatment can be maintained.
[0036] Furthermore, the interlayer film according to the present invention can improve the penetration resistance of laminated glass.
[0037] The interlayer film according to the present invention has a one-layer structure or a two or more layer structure. The interlayer film according to the present invention may have a one-layer structure, a two-layer structure, a two or more layer structure, a three-layer structure, a three or more layer structure, or a four or more layer structure. The interlayer film according to the present invention has a first layer. The interlayer film according to the present invention may be a single-layer interlayer film having only the first layer, or may be a multi-layer interlayer film having the first layer and another layer.
[0038] The intermediate film may have a structure of two or more layers, and may include a second layer in addition to the first layer. When the intermediate film includes the second layer, the second layer is disposed on the first surface side of the first layer.
[0039] When the interlayer film is a multilayer interlayer film having a structure of two or more layers, the interlayer film has a first surface layer and a second surface layer.
[0040] The intermediate film preferably comprises the first layer as a surface layer in the intermediate film. The first layer is preferably a surface layer of the intermediate film. The intermediate film preferably comprises the first layer as the first surface layer, and more preferably comprises the first layer as the first surface layer and the second surface layer. In this case, the effect of the present invention can be more effectively exhibited. Note that when the intermediate film is a single-layer intermediate film comprising only the first layer, the first layer is a surface layer.
[0041] The intermediate film may have a structure of three or more layers, and may include a third layer in addition to the first layer and the second layer. When the intermediate film includes the third layer, the third layer is disposed on the surface of the second layer opposite to the first layer.
[0042] The compression creep test carried out in the present invention will now be described in more detail.
[0043] Test sample A is a test sample with a diameter of 8 mm and a thickness of 0.8 mm obtained by cutting out the first layer. The test sample A can be prepared by peeling the layer to be measured (the first layer) from the interlayer film, and then press molding at 150°C. Test sample A is prepared to perform a compression creep test.
[0044] The test sample B is made using a first layer having a thickness of 200 μm or more and 900 μm or less. The thickness of the first layer is T B When the thickness of the first layer is 1 μm, the test sample B has a diameter of 8 mm and a thickness of T B The thickness of the first layer is the same as that of the test sample B.
[0045] The test sample C is prepared using an interlayer having a thickness of 80 μm or more and 1600 μm or less. The thickness of the interlayer is T C When the thickness is 1 μm, the test sample C is cut out from the interlayer film and has a diameter of 8 mm and a thickness of T CThe thickness of the intermediate film is the same as that of the test sample C.
[0046] In the compression creep test, the test samples A, B, and C are placed between a first jig having a circular surface with a diameter of 8 mm and a second jig having a circular surface with a diameter of 8 mm. With a load of 410 g applied in the thickness direction of the test samples A, B, and C, the temperature is raised from 30°C to 90°C at a rate of 6°C / min, and the test samples are held at 90°C for 5 minutes. The absolute value of the difference between the thickness of the test samples A, B, and C at 30°C immediately after holding at 30°C for 5 minutes or 30 minutes before starting the compression creep test and the thickness of the test samples A, B, and C immediately after holding at 90°C for 5 minutes at the end of the compression creep test is the change in thickness of the test samples A, B, and C before and after the compression creep test. Note that the thickness of the test samples A, B, and C after the compression creep test is usually smaller than the thickness of the test samples A, B, and C before the compression creep test.
[0047] An example of a device that can be used in the compression creep test is a viscoelasticity measuring device (TA Instruments' "RSA-G2"). The thicknesses of test samples A, B, and C before and after the compression test can be measured by monitoring the gap between the compression measurement jigs of the viscoelasticity measuring device. When using the RSA-G2, it is recommended to set the transducer mode to spring before performing the measurement.
[0048] When the interlayer film is subjected to the compressive creep test for test sample A, the change in thickness of test sample A before and after the compressive creep test is 50 μm or more and 325 μm or less. If the change is less than 50 μm, the transparency of the laminated glass is likely to decrease. If the change is more than 325 μm, bubbles are likely to occur at the edges of the laminated glass.
[0049] The change in thickness of the test sample A before and after the compression creep test is preferably 75 μm or more, more preferably 100 μm or more, and preferably 300 μm or less, more preferably 250 μm or less. When the change is equal to or more than the lower limit, the transparency of the laminated glass can be further improved. When the change is equal to or less than the upper limit, the generation of bubbles at the edge of the laminated glass can be further effectively suppressed.
[0050] When the interlayer film is subjected to the compressive creep test for test sample B, the change in thickness of test sample B before and after the compressive creep test is 50 μm or more and 325 μm or less. If the change is less than 50 μm, the transparency of the laminated glass is likely to decrease. If the change is more than 325 μm, bubbles are likely to occur at the edge of the laminated glass.
[0051] The change in thickness of test sample B before and after the compression creep test is preferably 75 μm or more, more preferably 100 μm or more, and preferably 300 μm or less, more preferably 250 μm or less. When the change is equal to or more than the lower limit, the transparency of the laminated glass can be further increased. When the change is equal to or less than the upper limit, the generation of bubbles at the edge of the laminated glass can be further effectively suppressed.
[0052] When the interlayer film is subjected to the compressive creep test for test sample C, the change in thickness of test sample C before and after the compressive creep test is 50 μm or more and 325 μm or less. If the change is less than 50 μm, the transparency of the laminated glass is likely to decrease. If the change is more than 325 μm, bubbles are likely to occur at the edges of the laminated glass.
[0053] The change in thickness of the test sample C before and after the compression creep test is preferably 75 μm or more, more preferably 100 μm or more, and preferably 300 μm or less, more preferably 250 μm or less. When the change is equal to or more than the lower limit, the transparency of the laminated glass can be further increased. When the change is equal to or less than the upper limit, the generation of bubbles at the edge of the laminated glass can be further effectively suppressed.
[0054] The following methods can be used to control the amount of change in thickness of test samples A, B, and C before and after the compression creep test to within the above-mentioned preferred range, etc. (1) Increasing the average degree of polymerization of the thermoplastic resin contained in the first layer or the interlayer film reduces the amount of change. (2) Increasing the content of plasticizer contained in the first layer or the interlayer film increases the amount of change. (3) Increasing the hydrogen bonding strength of the resin contained in the first layer or the interlayer film reduces the amount of change. By appropriately combining these methods, the amount of change can be controlled to within the above-mentioned preferred range, etc.
[0055] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings.
[0056] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of an interlayer film for laminated glass according to a first embodiment of the present invention.
[0057] The interlayer film 11 shown in FIG. 1 is a multi-layer interlayer film having a structure of two or more layers. The interlayer film 11 is used to obtain laminated glass. The interlayer film 11 is an interlayer film for laminated glass. The interlayer film 11 includes a first surface layer 1, an intermediate layer 3, and a second surface layer 2. The interlayer film 11 has a three-layer structure. The intermediate layer 3 is disposed and laminated on the first surface 1a of the first surface layer 1. The intermediate layer 3 is disposed and laminated on the first surface 2a of the second surface layer 2. The first surface layer 1 and the second surface layer 2 are the first layers. The second layer, which is the intermediate layer 3, is disposed on the first surface side of the first layer, which is the surface layer. The intermediate layer 3 is disposed and sandwiched between the first surface layer 1 and the second surface layer 2. Therefore, the intermediate film 11 has a multilayer structure (first layer / second layer / first layer) in which a first layer, a second layer, and a first layer are laminated in this order. In this case, the two first layers may be distinguished and referred to as a first layer A and a first layer B.
[0058] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of an interlayer film for laminated glass according to a second embodiment of the present invention.
[0059] The interlayer film 11A shown in Fig. 2 is a single-layer interlayer film having a one-layer structure. The interlayer film 11A is a first layer. The interlayer film 11A is used to obtain laminated glass. The interlayer film 11A is an interlayer film for laminated glass.
[0060] FIG. 3 is a cross-sectional view that illustrates an interlayer film for laminated glass according to a third embodiment of the present invention.
[0061] The intermediate film 11B shown in FIG. 3 is a multi-layered intermediate film having a structure of two or more layers. The intermediate film 11B is used to obtain laminated glass. The intermediate film 11B is an intermediate film for laminated glass. The intermediate film 11B includes a first surface layer 1B, a second intermediate layer 4B, a first intermediate layer 3B, a third intermediate layer 5B, and a second surface layer 2B. The intermediate film 11B has a five-layer structure. The second intermediate layer 4B is disposed on the first surface 1Ba of the first surface layer 1B and laminated thereon. The third intermediate layer 5B is disposed on the first surface 2Ba of the second surface layer 2B and laminated thereon. The first surface layer 1B and the second surface layer 2B are each the first layer. The second layer, which is the second intermediate layer 4B, is disposed on the first surface 1Ba side of the first layer, which is the first surface layer 1B. A third layer, which is a third intermediate layer 5B, is disposed on the first surface 2Ba side of the first layer, which is the second surface layer 2B. A functional film, which is a first intermediate layer 3B, is disposed and sandwiched between the second intermediate layer 4B and the third intermediate layer 5B. In this embodiment, the functional film is a light control film. Therefore, the intermediate film 11B has a multilayer structure (first layer / second layer / functional film / third layer / first layer) in which the first layer, the second layer, the functional film, the third layer, and the first layer are laminated in this order. In this case, the two first layers may be distinguished and called the first layer A and the first layer B.
[0062] The glass transition temperature of the first layer or the surface layer is preferably 20° C. or higher, more preferably 25° C. or higher, and even more preferably 30° C. or higher, and is preferably 45° C. or lower, more preferably 40° C. or lower, and even more preferably 35° C. or lower. When the glass transition temperature of the first layer or the surface layer is equal to or higher than the lower limit and equal to or lower than the upper limit, the effects of the present invention can be more effectively exhibited. Furthermore, when the glass transition temperature of the first layer or the surface layer is equal to or lower than the upper limit, the penetration resistance of the laminated glass can be further improved.
[0063] The softening point of the first layer or the surface layer is preferably 45° C. or higher, more preferably 50° C. or higher, and preferably 70° C. or lower, more preferably 65° C. or lower. When the softening point of the first layer or the surface layer is equal to or higher than the lower limit and equal to or lower than the upper limit, the effects of the present invention can be more effectively exhibited. Furthermore, when the softening point of the first layer or the surface layer is equal to or lower than the upper limit, the penetration resistance of the laminated glass can be further improved.
[0064] The glass transition temperature and the softening point are determined by viscoelasticity measurement. Specifically, the viscoelasticity measurement is carried out as follows.
[0065] The test piece is stored for 12 hours in an environment with a room temperature of 23±2°C and a humidity of 25±5%. The viscoelasticity is then measured using a TA Instruments viscoelasticity measuring device "ARES-G2". Using a parallel plate with a diameter of 8 mm as a jig, measurements are performed under the following conditions: shear mode, temperature drop rate of 3°C / min from 100°C to -20°C, frequency of 1Hz, and strain of 1%. In the measurement results obtained, the peak temperature of the loss tangent is taken as the glass transition temperature Tg (°C). The temperature at which the loss tangent value is minimal in the temperature range between Tg (°C) and 100°C is taken as the softening point.
[0066] The viscoelasticity measurement may be performed using the interlayer film itself. In this case, the peak of tan δ derived from the first layer may be read from the measurement results. For an interlayer film having a structure of two or more layers, each layer may be peeled off and the glass transition temperature of the layer to be measured may be measured. In the case of laminated glass, the laminated glass may be cooled with liquid nitrogen or the like, and then the laminated glass member and the interlayer film may be peeled off, and the viscoelasticity measurement may be performed using the peeled interlayer film.
[0067] The interlayer film according to the present invention, the first layer, the second layer, and the third layer, as well as each component used in the interlayer film, will be described in detail below.
[0068] (thermoplastic resin) The intermediate film preferably contains a thermoplastic resin (hereinafter, may be referred to as thermoplastic resin (0)). Examples of the thermoplastic resin include polyvinyl acetate resin, polyester resin, polyvinyl acetal resin, vinyl acetate resin, polystyrene resin, ethylene-vinyl acetate copolymer resin, ethylene-acrylic acid copolymer resin, polyurethane resin, ionomer resin, polyvinyl alcohol resin, polyolefin resin such as aliphatic polyolefin, and (meth)acrylic resin (polymer having a (meth)acryloyl group). Polyoxymethylene (or polyacetal) resin is included in polyvinyl acetal resin. Thermoplastic resins other than these may be used as the thermoplastic resin. The thermoplastic resin may be a thermoplastic elastomer.
[0069] The intermediate film preferably contains a polyvinyl acetal resin (hereinafter, may be referred to as polyvinyl acetal resin (0)) as the thermoplastic resin (0). The thermoplastic resin (0) contained in the intermediate film is preferably polyvinyl acetal resin (0). The first layer (including a single-layer intermediate film) preferably contains a thermoplastic resin (hereinafter, may be referred to as thermoplastic resin (1)). The first layer preferably contains a polyvinyl acetal resin (hereinafter, may be referred to as polyvinyl acetal resin (1)) as the thermoplastic resin (1). The thermoplastic resin (1) contained in the first layer is preferably polyvinyl acetal resin (1). The second layer preferably contains a thermoplastic resin (hereinafter, may be referred to as thermoplastic resin (2)). The second layer preferably contains a polyvinyl acetal resin (hereinafter, may be referred to as polyvinyl acetal resin (2)) or a polyester resin as the thermoplastic resin (2). The thermoplastic resin (2) contained in the second layer is preferably a polyvinyl acetal resin (2) or a polyester resin. The third layer preferably contains a thermoplastic resin (hereinafter, may be referred to as a thermoplastic resin (3)) or a polyester resin. The third layer preferably contains a polyvinyl acetal resin (hereinafter, may be referred to as a polyvinyl acetal resin (3)) or a polyester resin as the thermoplastic resin (3). The thermoplastic resin (3) contained in the third layer is preferably a polyvinyl acetal resin (3) or a polyester resin. The thermoplastic resin (1), the thermoplastic resin (2), and the thermoplastic resin (3) may be the same or different. Since sound insulation is further improved, the thermoplastic resin (1) is preferably different from the thermoplastic resin (2) and the thermoplastic resin (3). The polyvinyl acetal resin (1), the polyvinyl acetal resin (2), and the polyvinyl acetal resin (3) may be the same or different. Since the sound insulation property is further improved, it is preferable that the polyvinyl acetal resin (1) is different from the polyvinyl acetal resin (2) and the polyvinyl acetal resin (3).The thermoplastic resin (0), the thermoplastic resin (1), the thermoplastic resin (2), and the thermoplastic resin (3) may each be used alone or in combination of two or more thereof. The polyvinyl acetal resin (0), the polyvinyl acetal resin (1), the polyvinyl acetal resin (2), and the polyvinyl acetal resin (3) may each be used alone or in combination of two or more thereof.
[0070] The polyvinyl acetal resin can be produced, for example, by acetalizing polyvinyl alcohol (PVA) with an aldehyde. The polyvinyl acetal resin is preferably an acetalized product of polyvinyl alcohol. The polyvinyl alcohol can be obtained, for example, by saponifying polyvinyl acetate. The degree of saponification of the polyvinyl alcohol is generally within the range of 70 mol% to 99.9 mol%.
[0071] The average degree of polymerization of the polyvinyl alcohol (PVA) is preferably 200 or more, more preferably 500 or more, even more preferably 1500 or more, even more preferably 1600 or more, particularly preferably 2600 or more, and most preferably 2700 or more, and is preferably 5000 or less, more preferably 4000 or less, and even more preferably 3500 or less. When the average degree of polymerization is equal to or more than the lower limit, the penetration resistance of the laminated glass is further improved. When the average degree of polymerization is equal to or less than the upper limit, the interlayer film is easily formed.
[0072] The average degree of polymerization of the polyvinyl alcohol is determined by a method in accordance with JIS K6726 "Testing method for polyvinyl alcohol."
[0073] The polyvinyl acetal resin (1) may be a mixture of two or more polyvinyl acetal resins having different average degrees of polymerization of polyvinyl alcohol. In this case, the polyvinyl acetal resin (1) is preferably a mixture of a first polyvinyl acetal resin (1A) having an average degree of polymerization of polyvinyl alcohol of 1500 or more and a second polyvinyl acetal resin (1B) having an average degree of polymerization of polyvinyl alcohol of 1000 or less.
[0074] The average polymerization degree of the polyvinyl alcohol in the polyvinyl acetal resin (1) is preferably 900 or more, more preferably 1000 or more, and is preferably 1400 or less, more preferably 1300 or less.
[0075] The average polymerization degree of the polyvinyl alcohol in the first polyvinyl acetal resin (1A) is preferably 1500 or more, more preferably 1600 or more, and preferably 2000 or less, more preferably 1800 or less.
[0076] The average polymerization degree of the polyvinyl alcohol in the second polyvinyl acetal resin (1B) is preferably 400 or more, more preferably 500 or more, and preferably 1000 or less, more preferably 900 or less.
[0077] When a mixture of two or more polyvinyl acetal resins (1A) and (1B) having different average polymerization degrees of polyvinyl alcohol is used, the absolute value of the difference in the average polymerization degrees is preferably 500 or more, more preferably 600 or more, and preferably 1200 or less, more preferably 1100 or less.
[0078] In the total of 100% by weight of the first polyvinyl acetal resin (1A) and the second polyvinyl acetal resin (1B), the content of the second polyvinyl acetal resin (1B) is preferably 20% by weight or more, more preferably 25% by weight or more, and preferably 80% by weight or less, more preferably 75% by weight or less. When the content of the second polyvinyl acetal resin (1B) is equal to or more than the lower limit and equal to or less than the upper limit, the effects of the present invention can be more effectively exhibited.
[0079] The number of carbon atoms of the acetal group contained in the polyvinyl acetal resin is not particularly limited. The aldehyde used in producing the polyvinyl acetal resin is not particularly limited. The number of carbon atoms of the acetal group in the polyvinyl acetal resin is preferably 3 to 5, more preferably 3 or 4. When the number of carbon atoms of the acetal group in the polyvinyl acetal resin is 3 or more, the glass transition temperature of the interlayer film becomes sufficiently low. The number of carbon atoms of the acetal group in the polyvinyl acetal resin may be 4 or 5.
[0080] The aldehyde is not particularly limited. In general, an aldehyde having 1 to 10 carbon atoms is preferably used. Examples of the aldehyde having 1 to 10 carbon atoms include propionaldehyde, n-butylaldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexylaldehyde, n-octylaldehyde, n-nonylaldehyde, n-decylaldehyde, formaldehyde, acetaldehyde, and benzaldehyde. The aldehyde is preferably propionaldehyde, n-butylaldehyde, isobutyraldehyde, n-hexylaldehyde, or n-valeraldehyde, more preferably propionaldehyde, n-butylaldehyde, or isobutyraldehyde, and even more preferably n-butylaldehyde. The aldehydes may be used alone or in combination of two or more.
[0081] The intermediate film preferably contains a polyvinyl butyral resin as the thermoplastic resin (0). The intermediate film preferably contains a polyvinyl butyral resin as the polyvinyl acetal resin (0). The thermoplastic resin (0) contained in the intermediate film is preferably a polyvinyl butyral resin. The first layer preferably contains a polyvinyl butyral resin as the thermoplastic resin (1). The first layer preferably contains a polyvinyl butyral resin as the polyvinyl acetal resin (1). The thermoplastic resin (1) contained in the first layer is preferably a polyvinyl butyral resin. The second layer preferably contains a polyvinyl butyral resin as the thermoplastic resin (2). The second layer preferably contains a polyvinyl butyral resin as the polyvinyl acetal resin (2). The thermoplastic resin (2) contained in the second layer is preferably a polyvinyl butyral resin. The third layer preferably contains a polyvinyl butyral resin as the thermoplastic resin (3). The third layer preferably contains a polyvinyl butyral resin as the polyvinyl acetal resin (3). The thermoplastic resin (3) contained in the third layer is preferably a polyvinyl butyral resin. The polyvinyl butyral resins contained in the intermediate film, the first layer, the second layer, and the third layer may each be of one type or two or more types in combination.
[0082] The hydroxyl group content (hydroxyl group amount) of the polyvinyl acetal resin (0) is preferably 15 mol% or more, more preferably 18 mol% or more, and preferably 40 mol% or less, more preferably 35 mol% or less. When the hydroxyl group content is equal to or more than the lower limit, the adhesive strength of the interlayer film is further increased. When the hydroxyl group content is equal to or less than the upper limit, the flexibility of the interlayer film is increased, making it easier to handle.
[0083] The hydroxyl group content (hydroxyl group amount) of the polyvinyl acetal resin (1) is preferably 25 mol% or more, more preferably 28 mol% or more, more preferably 30 mol% or more, even more preferably 31.5 mol% or more, even more preferably 32 mol% or more, and particularly preferably 33 mol% or more. The hydroxyl group content (hydroxyl group amount) of the polyvinyl acetal resin (1) is preferably 38 mol% or less, more preferably 37 mol% or less, even more preferably 36.5 mol% or less, and particularly preferably 36 mol% or less. When the hydroxyl group content is the lower limit or more, the adhesive strength of the interlayer film is further increased. Also, when the hydroxyl group content is the upper limit or less, the flexibility of the interlayer film is increased, and the handling of the interlayer film is facilitated.
[0084] The hydroxyl group content of each of the polyvinyl acetal resin (2) and the polyvinyl acetal resin (3) is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 17 mol% or more, and is preferably 25 mol% or less, more preferably 20 mol% or less, even more preferably 19 mol% or less, and particularly preferably 18 mol% or less. When the hydroxyl group content is equal to or more than the lower limit, the mechanical strength of the interlayer film is further increased. In particular, when the hydroxyl group content of the polyvinyl acetal resins (2) and (3) is 15 mol% or more, the reaction efficiency is high and the productivity is excellent, and when it is 25 mol% or less, the sound insulation of the laminated glass is further increased. In addition, when the hydroxyl group content is equal to or less than the upper limit, the flexibility of the interlayer film is increased, and the handling of the interlayer film is facilitated.
[0085] From the viewpoint of further improving the sound insulation, the hydroxyl group content of the polyvinyl acetal resin (1) is preferably higher than the hydroxyl group content of the polyvinyl acetal resin (2). From the viewpoint of further improving the sound insulation, the hydroxyl group content of the polyvinyl acetal resin (1) is preferably higher than the hydroxyl group content of the polyvinyl acetal resin (3). From the viewpoint of further improving the sound insulation, the absolute value of the difference between the hydroxyl group content of the polyvinyl acetal resin (1) and the hydroxyl group content of the polyvinyl acetal resin (2) is preferably 1 mol % or more, more preferably 5 mol % or more, even more preferably 9 mol % or more, particularly preferably 10 mol % or more, and most preferably 12 mol % or more. From the viewpoint of further improving sound insulation, the absolute value of the difference between the hydroxyl content of the polyvinyl acetal resin (1) and the hydroxyl content of the polyvinyl acetal resin (3) is preferably 1 mol% or more, more preferably 5 mol% or more, even more preferably 9 mol% or more, particularly preferably 10 mol% or more, and most preferably 12 mol% or more. The absolute value of the difference between the hydroxyl content of the polyvinyl acetal resin (1) and the hydroxyl content of the polyvinyl acetal resin (2), and the absolute value of the difference between the hydroxyl content of the polyvinyl acetal resin (1) and the hydroxyl content of the polyvinyl acetal resin (3) are preferably 20 mol% or less.
[0086] The hydroxyl content of the polyvinyl acetal resin is a molar fraction calculated by dividing the amount of ethylene groups to which hydroxyl groups are bonded by the total amount of ethylene groups in the main chain, and expressed as a percentage. The amount of ethylene groups to which hydroxyl groups are bonded can be measured, for example, in accordance with JIS K6728 "Testing Methods for Polyvinyl Butyral."
[0087] The degree of acetylation (amount of acetyl groups) of the polyvinyl acetal resin (0) is preferably 0.1 mol% or more, more preferably 0.3 mol% or more, even more preferably 0.5 mol% or more, and is preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 20 mol% or less. When the degree of acetylation is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetylation is equal to or less than the upper limit, the moisture resistance of the interlayer film and the laminated glass is increased.
[0088] The degree of acetylation (amount of acetyl groups) of the polyvinyl acetal resin (1) is preferably 0.01 mol% or more, more preferably 0.5 mol% or more, and preferably 10 mol% or less, more preferably 2 mol% or less. When the degree of acetylation is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetylation is equal to or less than the upper limit, the moisture resistance of the interlayer film and the laminated glass is increased.
[0089] The degree of acetylation of each of the polyvinyl acetal resin (2) and the polyvinyl acetal resin (3) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, even more preferably 7 mol% or more, even more preferably 9 mol% or more, and preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 24 mol% or less, and particularly preferably 20 mol% or less. When the degree of acetylation is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetylation is equal to or less than the upper limit, the moisture resistance of the interlayer film and the laminated glass is increased. In particular, when the degree of acetylation of the polyvinyl acetal resins (2) and (3) is 0.1 mol% or more and 25 mol% or less, the penetration resistance is excellent.
[0090] The degree of acetylation is a molar fraction calculated by dividing the amount of ethylene groups to which acetyl groups are bonded by the total amount of ethylene groups in the main chain, expressed as a percentage. The amount of ethylene groups to which acetyl groups are bonded can be measured, for example, in accordance with JIS K6728 "Testing Methods for Polyvinyl Butyral."
[0091] The degree of acetalization of the polyvinyl acetal resin (0) (the degree of butyralization in the case of a polyvinyl butyral resin) is preferably 60 mol% or more, more preferably 63 mol% or more, and preferably 85 mol% or less, more preferably 75 mol% or less, and even more preferably 70 mol% or less. When the degree of acetalization is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetalization is equal to or less than the upper limit, the reaction time required to produce the polyvinyl acetal resin is shortened.
[0092] The degree of acetalization of the polyvinyl acetal resin (1) (the degree of butyralization in the case of a polyvinyl butyral resin) is preferably 55 mol% or more, more preferably 60 mol% or more, and preferably 75 mol% or less, more preferably 71 mol% or less. When the degree of acetalization is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetalization is equal to or less than the upper limit, the reaction time required to produce the polyvinyl acetal resin is shortened.
[0093] The degree of acetalization of each of the polyvinyl acetal resin (2) and the polyvinyl acetal resin (3) (the degree of butyralization in the case of a polyvinyl butyral resin) is preferably 47 mol% or more, more preferably 60 mol% or more, and preferably 85 mol% or less, more preferably 80 mol% or less, and even more preferably 75 mol% or less. When the degree of acetalization is equal to or more than the lower limit, the compatibility of the polyvinyl acetal resin with the plasticizer is increased. When the degree of acetalization is equal to or less than the upper limit, the reaction time required to produce the polyvinyl acetal resin is shortened.
[0094] The degree of acetalization is determined as follows. First, the amount of ethylene groups to which hydroxyl groups are bonded and the amount of ethylene groups to which acetyl groups are bonded are subtracted from the total amount of ethylene groups in the main chain to determine a value. The obtained value is divided by the total amount of ethylene groups in the main chain to determine a molar fraction. The value expressed as a percentage of this molar fraction is the degree of acetalization.
[0095] The hydroxyl group content (hydroxyl group amount), acetalization degree (butyralization degree), and acetylation degree are preferably calculated from the results measured by a method conforming to JIS K6728 "Testing Method for Polyvinyl Butyral". However, measurements according to ASTM D1396-92 may also be used. When the polyvinyl acetal resin is a polyvinyl butyral resin, the hydroxyl group content (hydroxyl group amount), acetalization degree (butyralization degree), and acetylation degree can be calculated from the results measured by a method conforming to JIS K6728 "Testing Method for Polyvinyl Butyral".
[0096] The content of polyvinyl acetal resin in 100% by weight of thermoplastic resin contained in the interlayer is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, particularly preferably 80% by weight or more, and most preferably 90% by weight or more. The content of polyvinyl acetal resin in 100% by weight of thermoplastic resin contained in the interlayer is preferably 100% by weight or less. The main component (50% by weight or more) of the thermoplastic resin of the interlayer is preferably polyvinyl acetal resin.
[0097] The content of polyvinyl acetal resin in 100% by weight of the thermoplastic resin contained in the first layer is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, particularly preferably 80% by weight or more, and most preferably 90% by weight or more. The content of polyvinyl acetal resin in 100% by weight of the thermoplastic resin contained in the first layer is preferably 100% by weight or less. The main component (50% by weight or more) of the thermoplastic resin of the first layer is preferably polyvinyl acetal resin.
[0098] (Plasticizer) The interlayer preferably contains a plasticizer. The first layer (including a single-layer interlayer) preferably contains a plasticizer (hereinafter, may be referred to as plasticizer (1)). The second layer preferably contains a plasticizer (hereinafter, may be referred to as plasticizer (2)). The third layer preferably contains a plasticizer (hereinafter, may be referred to as plasticizer (3)). By using a plasticizer or by using a polyvinyl acetal resin and a plasticizer in combination, the impact resistance and penetration resistance are further improved, and the adhesive strength of the layer containing the polyvinyl acetal resin and the plasticizer to the laminated glass member or other layers is appropriately increased. The plasticizer is not particularly limited. The plasticizer (1), the plasticizer (2), and the plasticizer (3) may be the same or different. The plasticizer (1), the plasticizer (2), and the plasticizer (3) may each be used alone or in combination of two or more.
[0099] The plasticizer may be an organic ester plasticizer such as a monobasic organic acid ester or a polybasic organic acid ester, or an organic phosphoric acid plasticizer such as an organic phosphoric acid plasticizer or an organic phosphorous acid plasticizer. The plasticizer is preferably an organic ester plasticizer. The plasticizer is preferably a liquid plasticizer.
[0100] The monobasic organic acid ester may be a glycol ester obtained by reacting a glycol with a monobasic organic acid. The glycol may be triethylene glycol, tetraethylene glycol, or tripropylene glycol. The monobasic organic acid may be butyric acid, isobutyric acid, caproic acid, 2-ethylbutyric acid, heptyl acid, n-octylic acid, 2-ethylhexyl acid, n-nonylic acid, decylic acid, or benzoic acid.
[0101] Examples of the polybasic organic acid ester include ester compounds of a polybasic organic acid and an alcohol having a linear or branched structure with 4 to 8 carbon atoms. Examples of the polybasic organic acid include adipic acid, sebacic acid, and azelaic acid.
[0102] Examples of the organic ester plasticizer include triethylene glycol di-2-ethylpropanoate, triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol dicaprylate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, 1,4-butylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylbutylate, and ethylene glycol di-2-ethylbutylate. ester, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylpentanoate, tetraethylene glycol di-2-ethylbutyrate, diethylene glycol dicaprylate, diethylene glycol dibenzoate, dipropylene glycol dibenzoate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, a mixture of heptyl adipate and nonyl adipate, diisononyl adipate, diisodecyl adipate, heptylnonyl adipate, dibutyl sebacate, oil-modified alkyd sebacate, and a mixture of a phosphoric acid ester and an adipate. Organic ester plasticizers other than these may also be used. Adipic acid esters other than the above-mentioned adipic acid esters may also be used.
[0103] The organic phosphoric acid plasticizers include tributoxyethyl phosphate, isodecylphenyl phosphate, and triisopropyl phosphate.
[0104] The plasticizer is preferably a diester plasticizer represented by the following formula (1).
[0105] [ka]
[0106] In the above formula (1), R1 and R2 each represent an organic group having 2 to 10 carbon atoms, R3 represents an ethylene group, an isopropylene group, or an n-propylene group, and p represents an integer of 3 to 10. In the above formula (1), R1 and R2 each represent an organic group having 5 to 10 carbon atoms, and more preferably an organic group having 6 to 10 carbon atoms.
[0107] The plasticizer preferably includes triethylene glycol di-2-ethylhexanoate (3GO), triethylene glycol di-2-ethylbutyrate (3GH) or triethylene glycol di-2-ethylpropanoate. The plasticizer more preferably includes triethylene glycol di-2-ethylhexanoate (3GO) or triethylene glycol di-2-ethylbutyrate (3GH), and even more preferably includes triethylene glycol di-2-ethylhexanoate.
[0108] In the first layer, the content of the plasticizer (1) relative to 100 parts by weight of the thermoplastic resin (1) (when the thermoplastic resin (1) is a polyvinyl acetal resin (1), 100 parts by weight of the polyvinyl acetal resin (1)) is defined as the content (1). The content (1) is preferably 20 parts by weight or more, more preferably 25 parts by weight or more, even more preferably 28 parts by weight or more, and preferably 40 parts by weight or less, more preferably 38 parts by weight or less, even more preferably 35 parts by weight or less, and particularly preferably 33 parts by weight or less. When the content (1) is equal to or more than the lower limit, the flexibility of the interlayer film is increased, and the handling of the interlayer film is facilitated. When the content (1) is equal to or more than the lower limit, the flexibility of the interlayer film is increased, and the handling of the interlayer film is facilitated. When the content (1) is equal to or less than the upper limit, the bending rigidity is further increased. When the content (1) is equal to or more than the lower limit and equal to or less than the upper limit, the effects of the present invention can be exhibited more effectively.
[0109] In the second layer, the content of the plasticizer (2) relative to 100 parts by weight of the thermoplastic resin (2) (when the thermoplastic resin (2) is a polyvinyl acetal resin (2), 100 parts by weight of the polyvinyl acetal resin (2)) is defined as the content (2). The content (2) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more, even more preferably 60 parts by weight or more, and is preferably 100 parts by weight or less, more preferably 90 parts by weight or less, even more preferably 85 parts by weight or less, and particularly preferably 80 parts by weight or less. When the content (2) is equal to or more than the lower limit, the flexibility of the interlayer film is increased, and the interlayer film is easy to handle. When the content (2) is equal to or less than the upper limit, the penetration resistance of the laminated glass is further increased.
[0110] In the third layer, the content of the plasticizer (3) relative to 100 parts by weight of the thermoplastic resin (3) (when the thermoplastic resin (3) is a polyvinyl acetal resin (3), 100 parts by weight of the polyvinyl acetal resin (3)) is defined as the content (3). The content (3) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more, even more preferably 60 parts by weight or more, and is preferably 100 parts by weight or less, more preferably 90 parts by weight or less, even more preferably 85 parts by weight or less, and particularly preferably 80 parts by weight or less. When the content (3) is equal to or more than the lower limit, the flexibility of the interlayer film is increased, and the interlayer film is easy to handle. When the content (3) is equal to or less than the upper limit, the penetration resistance of the laminated glass is further increased.
[0111] The content (1) and the content (2) may be the same or different. The content (1) and the content (3) may be the same or different. From the viewpoint of improving the sound insulation of the laminated glass, it is preferable that the content (1) and the content (2) are the same, or the content (1) is less than the content (2), and it is more preferable that the content (1) is less than the content (2). From the viewpoint of improving the sound insulation of the laminated glass, it is preferable that the content (1) and the content (3) are the same, or the content (1) is less than the content (3), and it is more preferable that the content (1) is less than the content (3).
[0112] From the viewpoint of further improving the sound insulation of the laminated glass, the absolute value of the difference between the content (2) and the content (1) and the absolute value of the difference between the content (3) and the content (1) are each preferably 10 parts by weight or more, more preferably 15 parts by weight or more, and even more preferably 20 parts by weight or more. The absolute value of the difference between the content (2) and the content (1) and the absolute value of the difference between the content (3) and the content (1) are each preferably 80 parts by weight or less, more preferably 75 parts by weight or less, and even more preferably 70 parts by weight or less.
[0113] (Heat-shielding material) The intermediate film preferably contains a heat-shielding material. The first layer (including a single-layer intermediate film) preferably contains a heat-shielding material. The second layer preferably contains a heat-shielding material. The third layer preferably contains a heat-shielding material. Only one type of the heat-shielding material may be used, or two or more types may be used in combination.
[0114] The heat-shielding material preferably contains at least one component X selected from a phthalocyanine compound, a naphthalocyanine compound, and an anthracyanine compound, or contains heat-shielding particles. In this case, the heat-shielding material may contain both the component X and the heat-shielding particles.
[0115] Ingredient X: The interlayer film preferably contains at least one component X selected from a phthalocyanine compound, a naphthalocyanine compound, and an anthracyanine compound. The first layer preferably contains the component X. The second layer preferably contains the component X. The third layer preferably contains the component X. The component X is a heat-shielding material. Only one type of the component X may be used, or two or more types may be used in combination.
[0116] There is no particular limitation on the above-mentioned component X. As the component X, a conventionally known phthalocyanine compound, naphthalocyanine compound, or anthracyanine compound can be used.
[0117] The component X may be phthalocyanine, a derivative of phthalocyanine, naphthalocyanine, a derivative of naphthalocyanine, an anthracyanine, or a derivative of anthracyanine. The phthalocyanine compound and the derivative of phthalocyanine each preferably have a phthalocyanine skeleton. The naphthalocyanine compound and the derivative of naphthalocyanine each preferably have a naphthalocyanine skeleton. The anthracyanine compound and the derivative of anthracyanine each preferably have an anthracyanine skeleton.
[0118] From the viewpoint of further improving the heat insulation properties of the interlayer film and laminated glass, the above-mentioned component X is preferably at least one selected from the group consisting of phthalocyanine, phthalocyanine derivatives, naphthalocyanine and naphthalocyanine derivatives, and more preferably at least one of phthalocyanine and phthalocyanine derivatives.
[0119] From the viewpoint of effectively increasing the heat shielding property and maintaining the visible light transmittance at a higher level for a long period of time, the above component X preferably contains a vanadium atom or a copper atom. The above component X preferably contains a vanadium atom, and also preferably contains a copper atom. The above component X is more preferably at least one of phthalocyanine containing a vanadium atom or a copper atom and a derivative of phthalocyanine containing a vanadium atom or a copper atom. From the viewpoint of further increasing the heat shielding property of the interlayer film and the laminated glass, the above component X preferably has a structural unit in which an oxygen atom is bonded to a vanadium atom.
[0120] In 100% by weight of the intermediate film or in 100% by weight of the layer containing the component X (first layer, second layer or third layer), the content of the component X is preferably 0.001% by weight or more, more preferably 0.005% by weight or more, even more preferably 0.01% by weight or more, and particularly preferably 0.02% by weight or more. In 100% by weight of the intermediate film or in 100% by weight of the layer containing the component X (first layer, second layer or third layer), the content of the component X is preferably 0.2% by weight or less, more preferably 0.1% by weight or less, even more preferably 0.05% by weight or less, and particularly preferably 0.04% by weight or less. When the content of the component X is the above lower limit or more and the above upper limit or less, the heat shielding property is sufficiently high and the visible light transmittance is sufficiently high. For example, it is possible to make the visible light transmittance 70% or more.
[0121] Heat shielding particles: The intermediate film preferably contains heat-shielding particles. The first layer preferably contains heat-shielding particles. The second layer preferably contains heat-shielding particles. The third layer preferably contains heat-shielding particles. The heat-shielding particles are a heat-shielding material. By using the heat-shielding particles, infrared rays (heat rays) can be effectively blocked. Only one type of the heat-shielding particles may be used, or two or more types may be used in combination.
[0122] From the viewpoint of further enhancing the heat shielding property of the laminated glass, the heat shielding particles are more preferably metal oxide particles.The heat shielding particles are preferably particles formed of a metal oxide (metal oxide particles).
[0123] Infrared rays, which have wavelengths of 780 nm or more, longer than visible light, have a smaller amount of energy than ultraviolet rays. However, infrared rays have a large thermal effect, and when infrared rays are absorbed by a substance, they are released as heat. For this reason, infrared rays are generally called heat rays. By using the above heat-shielding particles, infrared rays (heat rays) can be effectively blocked. Note that heat-shielding particles refer to particles that can absorb infrared rays.
[0124] Specific examples of the heat shielding particles include metal oxide particles such as aluminum-doped tin oxide particles, indium-doped tin oxide particles, antimony-doped tin oxide particles (ATO particles), gallium-doped zinc oxide particles (GZO particles), indium-doped zinc oxide particles (IZO particles), aluminum-doped zinc oxide particles (AZO particles), niobium-doped titanium oxide particles, sodium-doped tungsten oxide particles, cesium-doped tungsten oxide particles, thallium-doped tungsten oxide particles, rubidium-doped tungsten oxide particles, tin-doped indium oxide particles (ITO particles), tin-doped zinc oxide particles, and silicon-doped zinc oxide particles, as well as lanthanum hexaboride (LaB6) particles. Heat shielding particles other than these may also be used. Metal oxide particles are preferred because of their high heat ray shielding function, and ATO particles, GZO particles, IZO particles, ITO particles, or tungsten oxide particles are more preferred, with ITO particles or tungsten oxide particles being particularly preferred. In particular, tin-doped indium oxide particles (ITO particles) are preferred because they have a high heat ray shielding function and are easily available, and tungsten oxide particles are also preferred.
[0125] From the viewpoint of further improving the heat insulating properties of the interlayer film and the laminated glass, the tungsten oxide particles are preferably metal-doped tungsten oxide particles. The "tungsten oxide particles" include metal-doped tungsten oxide particles. Specific examples of the metal-doped tungsten oxide particles include sodium-doped tungsten oxide particles, cesium-doped tungsten oxide particles, thallium-doped tungsten oxide particles, and rubidium-doped tungsten oxide particles.
[0126] From the viewpoint of further increasing the heat insulating property of the interlayer film and the laminated glass, cesium-doped tungsten oxide particles are particularly preferred. From the viewpoint of further increasing the heat insulating property of the interlayer film and the laminated glass, the cesium-doped tungsten oxide particles are represented by the formula: Cs 0.33 Tungsten oxide particles represented by WO3 are preferred.
[0127] The average particle size of the heat shielding particles is preferably 0.01 μm or more, more preferably 0.02 μm or more, and is preferably 0.1 μm or less, more preferably 0.05 μm or less. When the average particle size is equal to or more than the lower limit, the heat shielding properties are sufficiently high. When the average particle size is equal to or less than the upper limit, the dispersibility of the heat shielding particles is high.
[0128] The "average particle size" refers to the volume average particle size. The average particle size can be measured using a particle size distribution measuring device (manufactured by Nikkiso Co., Ltd., "UPA-EX150") or the like.
[0129] In 100% by weight of the intermediate film or in 100% by weight of the layer containing the heat shielding particles (first layer, second layer or third layer), the content of each of the heat shielding particles (particularly the content of the tungsten oxide particles) is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, even more preferably 1% by weight or more, and particularly preferably 1.5% by weight or more. In 100% by weight of the intermediate film or in 100% by weight of the layer containing the heat shielding particles (first layer, second layer or third layer), the content of each of the heat shielding particles (particularly the content of the tungsten oxide particles) is preferably 6% by weight or less, more preferably 5.5% by weight or less, even more preferably 4% by weight or less, particularly preferably 3.5% by weight or less, and most preferably 3% by weight or less. When the content of the heat shielding particles is equal to or more than the lower limit and equal to or less than the upper limit, the heat shielding property is sufficiently high and the visible light transmittance is sufficiently high.
[0130] (Metal Salts) The interlayer preferably contains at least one metal salt selected from alkali metal salts, alkaline earth metal salts other than magnesium salts, and magnesium salts (hereinafter, may be referred to as metal salt M). In addition, since magnesium is an alkaline earth metal, the interlayer preferably contains at least one metal salt M selected from alkali metal salts and alkaline earth metal salts. The first layer preferably contains the metal salt M. The second layer preferably contains the metal salt M. The third layer preferably contains the metal salt M. The alkaline earth metals refer to six metals, namely, Be, Mg, Ca, Sr, Ba, and Ra. By using the metal salt M, it becomes easy to control the adhesion between the interlayer and a laminated glass member such as a glass plate, or the adhesion between each layer in the interlayer. The metal salt M may be used alone or in combination of two or more.
[0131] The metal salt M preferably contains at least one metal selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba. The metal salt contained in the interlayer film preferably contains at least one metal selected from the group consisting of K and Mg.
[0132] Moreover, the metal salt M is more preferably an alkali metal salt of an organic acid having 2 to 16 carbon atoms, an alkaline earth metal salt of an organic acid having 2 to 16 carbon atoms other than a magnesium salt of an organic acid having 2 to 16 carbon atoms, or a magnesium salt of an organic acid having 2 to 16 carbon atoms. Since magnesium is an alkaline earth metal, the metal salt M is preferably an alkali metal salt of an organic acid having 2 to 16 carbon atoms, or an alkaline earth metal salt of an organic acid having 2 to 16 carbon atoms. The metal salt M is further preferably a magnesium salt of a carboxylate having 2 to 16 carbon atoms, or a potassium salt of a carboxylate having 2 to 16 carbon atoms.
[0133] Examples of the magnesium salt of a carboxylate having 2 to 16 carbon atoms and the potassium salt of a carboxylate having 2 to 16 carbon atoms include magnesium acetate, potassium acetate, magnesium propionate, potassium propionate, magnesium 2-ethylbutyrate, potassium 2-ethylbutanoate, magnesium 2-ethylhexanoate, and potassium 2-ethylhexanoate.
[0134] The total content of Mg and K in the interlayer containing the metal salt M or in the layer (first layer, second layer or third layer) containing the metal salt M is preferably 5 ppm or more, more preferably 10 ppm or more, even more preferably 20 ppm or more, and is preferably 300 ppm or less, more preferably 250 ppm or less, even more preferably 200 ppm or less. When the total content of Mg and K is equal to or more than the above lower limit and equal to or less than the above upper limit, the adhesion between the interlayer and the laminated glass member (such as glass plates) or the adhesion between the layers in the interlayer can be more effectively controlled.
[0135] (UV protection agent) The interlayer film preferably contains an ultraviolet shielding agent. The first layer preferably contains an ultraviolet shielding agent. The second layer preferably contains an ultraviolet shielding agent. The third layer preferably contains an ultraviolet shielding agent. By using an ultraviolet shielding agent, the visible light transmittance is more unlikely to decrease even when the interlayer film and the laminated glass are used for a long period of time. Only one type of ultraviolet shielding agent may be used, or two or more types may be used in combination.
[0136] The ultraviolet shielding agent includes an ultraviolet absorbing agent. The ultraviolet shielding agent is preferably an ultraviolet absorbing agent.
[0137] Examples of the ultraviolet ray shielding agent include ultraviolet ray shielding agents containing metal atoms, ultraviolet ray shielding agents containing metal oxides, ultraviolet ray shielding agents having a benzotriazole structure (benzotriazole compounds), ultraviolet ray shielding agents having a benzophenone structure (benzophenone compounds), ultraviolet ray shielding agents having a triazine structure (triazine compounds), ultraviolet ray shielding agents having a malonic acid ester structure (malonic acid ester compounds), ultraviolet ray shielding agents having an oxalic acid anilide structure (oxalic acid anilide compounds), and ultraviolet ray shielding agents having a benzoate structure (benzoate compounds).
[0138] Examples of the ultraviolet shielding agent containing the metal atom include platinum particles, platinum particles whose surfaces are coated with silica, palladium particles, and palladium particles whose surfaces are coated with silica. The ultraviolet shielding agent is preferably not a heat shielding particle.
[0139] The ultraviolet shielding agent is preferably an ultraviolet shielding agent having a benzotriazole structure, an ultraviolet shielding agent having a benzophenone structure, an ultraviolet shielding agent having a triazine structure, or an ultraviolet shielding agent having a benzoate structure. The ultraviolet shielding agent is more preferably an ultraviolet shielding agent having a benzotriazole structure or an ultraviolet shielding agent having a benzophenone structure, and further preferably an ultraviolet shielding agent having a benzotriazole structure.
[0140] Examples of the ultraviolet shielding agent containing the metal oxide include zinc oxide, titanium oxide, and cerium oxide. Furthermore, the ultraviolet shielding agent containing the metal oxide may be surface-coated. Examples of the surface-coating material of the ultraviolet shielding agent containing the metal oxide include insulating metal oxides, hydrolyzable organic silicon compounds, and silicone compounds.
[0141] The insulating metal oxide includes silica, alumina, zirconia, etc. The insulating metal oxide has a band gap energy of, for example, 5.0 eV or more.
[0142] Examples of the ultraviolet shielding agent having the benzotriazole structure include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (BASF's "Tinuvin P"), 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole (BASF's "Tinuvin 320"), 2-(2'-hydroxy-3'-t-butyl-5-methylphenyl)-5-chlorobenzotriazole (BASF's "Tinuvin 326"), and 2-(2'-hydroxy-3',5'-di-amylphenyl)benzotriazole (BASF's "Tinuvin 328"), etc. Since the ultraviolet shielding agent has excellent ultraviolet shielding performance, it is preferable that the ultraviolet shielding agent has a benzotriazole structure containing a halogen atom, and more preferably has a benzotriazole structure containing a chlorine atom.
[0143] Examples of the ultraviolet screening agent having a benzophenone structure include octabenzone ("Chimassorb 81" manufactured by BASF).
[0144] Examples of the ultraviolet screening agent having a triazine structure include "LA-F70" manufactured by ADEKA Corporation and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol ("Tinuvin 1577FF" manufactured by BASF).
[0145] Examples of the ultraviolet screening agent having a malonic acid ester structure include dimethyl 2-(p-methoxybenzylidene)malonate, tetraethyl-2,2-(1,4-phenylenedimethylidene)bismalonate, and 2-(p-methoxybenzylidene)-bis(1,2,2,6,6-pentamethyl-4-piperidinyl)malonate.
[0146] Commercially available ultraviolet screening agents having the above malonic acid ester structure include Hostavin B-CAP, Hostavin PR-25, and Hostavin PR-31 (all manufactured by Clariant).
[0147] Examples of ultraviolet screening agents having the above-mentioned oxalic acid anilide structure include oxalic acid diamides having an aryl group substituted on the nitrogen atom, such as N-(2-ethylphenyl)-N'-(2-ethoxy-5-t-butylphenyl)oxalic acid diamide, N-(2-ethylphenyl)-N'-(2-ethoxy-phenyl)oxalic acid diamide, and 2-ethyl-2'-ethoxy-oxalanilide ("Sanduvor VSU" manufactured by Clariant).
[0148] Examples of the ultraviolet screening agent having a benzoate structure include 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate ("Tinuvin 120" manufactured by BASF).
[0149] In 100% by weight of the intermediate film or in 100% by weight of the layer (first layer, second layer or third layer) containing the ultraviolet ray shielding agent, the content of the ultraviolet ray shielding agent and the content of the benzotriazole compound are preferably 0.1% by weight or more, more preferably 0.2% by weight or more, even more preferably 0.3% by weight or more, and particularly preferably 0.5% by weight or more. In 100% by weight of the intermediate film or in 100% by weight of the layer (first layer, second layer or third layer) containing the ultraviolet ray shielding agent, the content of the ultraviolet ray shielding agent and the content of the benzotriazole compound are preferably 2.5% by weight or less, more preferably 2% by weight or less, even more preferably 1% by weight or less, and particularly preferably 0.8% by weight or less. When the content of the ultraviolet ray shielding agent is the above lower limit or more and the above upper limit or less, the decrease in visible light transmittance after a period of time can be further suppressed. In particular, by having the content of the ultraviolet ray shielding agent be 0.2% by weight or more in 100% by weight of the layer containing the ultraviolet ray shielding agent, it is possible to significantly suppress the decrease in visible light transmittance of the interlayer film and laminated glass over a period of time.
[0150] (Antioxidants) The intermediate film preferably contains an antioxidant. The first layer preferably contains an antioxidant. The second layer preferably contains an antioxidant. The third layer preferably contains an antioxidant. Only one type of antioxidant may be used, or two or more types may be used in combination.
[0151] The antioxidants include phenol-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants. The phenol-based antioxidants are antioxidants having a phenol skeleton. The sulfur-based antioxidants are antioxidants containing sulfur atoms. The phosphorus-based antioxidants are antioxidants containing phosphorus atoms.
[0152] The antioxidant is preferably a phenol-based antioxidant or a phosphorus-based antioxidant.
[0153] The phenol-based antioxidants include 2,6-di-t-butyl-p-cresol (BHT), butyl hydroxyanisole (BHA), 2,6-di-t-butyl-4-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis-(4-methyl-6-butylphenol), 2,2'-methylenebis-(4-ethyl-6-t-butylphenol), 4,4'-butylidene-bis-(3-methyl-6-t-butylphenol), 1,1,3-tris-(2-methyl-hydroxy-5- t-butylphenyl)butane, tetrakis[methylene-3-(3',5'-butyl-4-hydroxyphenyl)propionate]methane, 1,3,3-tris-(2-methyl-4-hydroxy-5-t-butylphenol)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,3'-t-butylphenol)butyric acid glycol ester, and bis(3-t-butyl-4-hydroxy-5-methylbenzenepropanoic acid)ethylenebis(oxyethylene). One or more of these antioxidants are preferably used.
[0154] Examples of the phosphorus-based antioxidant include tridecyl phosphite, tris(tridecyl)phosphite, triphenyl phosphite, trinonylphenyl phosphite, bis(tridecyl)pentaerythritol diphosphite, bis(decyl)pentaerythritol diphosphite, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butyl-6-methylphenyl)ethyl ester phosphorous acid, and 2,2'-methylenebis(4,6-di-t-butyl-1-phenyloxy)(2-ethylhexyloxy)phosphorus, etc. One or more of these antioxidants are preferably used.
[0155] Commercially available examples of the antioxidant include "IRGANOX 245" manufactured by BASF, "IRGAFOS 168" manufactured by BASF, "IRGAFOS 38" manufactured by BASF, "Sumilizer BHT" manufactured by Sumitomo Chemical Co., Ltd., "H-BHT" manufactured by Sakai Chemical Industry Co., Ltd., and "IRGANOX 1010" manufactured by BASF.
[0156] In order to maintain the high visible light transmittance of the interlayer film and the laminated glass for a long period of time, the content of the antioxidant in 100% by weight of the interlayer film or in 100% by weight of the layer containing the antioxidant (first layer, second layer or third layer) is preferably 0.1% by weight or more. In addition, since the effect of adding the antioxidant becomes saturated, the content of the antioxidant in 100% by weight of the interlayer film or in 100% by weight of the layer containing the antioxidant is preferably 2% by weight or less.
[0157] (Other ingredients) The intermediate film, the first layer, the second layer and the third layer may each contain additives such as coupling agents, dispersants, surfactants, flame retardants, antistatic agents, pigments, dyes, adhesion regulators other than metal salts, moisture resistant agents, fluorescent brighteners and infrared absorbing agents, as necessary. These additives may be used alone or in combination of two or more.
[0158] (functional film) The intermediate film may have a functional film for the purpose of realizing a specific function, such as a light control film, an infrared reflective film, a colored film, or a film with a printed design.
[0159] The light control film may be, for example, a film having an electrochromic layer and an electrolyte layer. The electrochromic layer is a layer containing an electrochromic compound (a compound having electrochromic properties). The term "electrochromic properties" means that the light transmittance is changed by applying a voltage.
[0160] Examples of the infrared reflective film include a resin film with a metal foil, a multilayer laminate film in which a metal layer and a dielectric layer are formed on a resin film, a multilayer resin film, a liquid crystal film, etc. These films have the ability to reflect infrared rays.
[0161] The resin film with metal foil includes a resin film and a metal foil laminated on the outer surface of the resin film. Examples of materials for the resin film include polyethylene terephthalate resin, polyethylene naphthalate resin, polyvinyl acetal resin, ethylene-vinyl acetate copolymer resin, ethylene-acrylic acid copolymer resin, polyurethane resin, polyvinyl alcohol resin, polyolefin resin, polyvinyl chloride resin, and polyimide resin. Examples of materials for the metal foil include aluminum, copper, silver, gold, palladium, and alloys containing these.
[0162] The multilayer laminate film in which a metal layer and a dielectric layer are formed on the resin film is a multilayer laminate film in which metal layers and dielectric layers are alternately laminated on a resin film in any number of layers. In the multilayer laminate film in which a metal layer and a dielectric layer are formed on the resin layer, it is preferable that all of the metal layers and dielectric layers are alternately laminated, but there may be a structural portion in which some of the layers are not alternately laminated, such as metal layer / dielectric layer / metal layer / dielectric layer / metal layer / metal layer / dielectric layer / metal layer.
[0163] Examples of the material of the resin film in the multi-layer laminate film include polyethylene, polypropylene, polylactic acid, poly(4-methylpentene-1), polyvinylidene fluoride, cyclic polyolefin, polymethyl methacrylate, polyvinyl chloride, polyvinyl alcohol, polyamides such as nylon 6, 11, 12, 66, polystyrene, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polyester, polyphenylene sulfide, and polyetherimide. Examples of the material of the metal layer in the multi-layer laminate film include the same material as the material of the metal foil in the resin film with metal foil. A coating layer of metal or mixed oxide of metals can be applied to both sides or one side of the metal layer. Examples of the material of the coating layer include ZnO, Al2O3, Ga2O3, InO3, MgO, Ti, NiCr, and Cu. Examples of the material of the dielectric layer in the multi-layer laminate film include indium oxide.
[0164] The multilayer resin film is a laminated film in which a plurality of resin films are laminated. Examples of materials for the multilayer resin film include materials similar to those for the resin films in the multilayer laminate film. The number of resin films laminated in the multilayer resin film is 2 or more, may be 3 or more, or may be 5 or more. The number of resin films laminated in the multilayer resin film may be 1000 or less, may be 100 or less, or may be 50 or less.
[0165] The multilayer resin film may be a multilayer resin film in which two or more types of thermoplastic resin layers having different optical properties (refractive indexes) are laminated alternately or randomly in any number of layers. Such a multilayer resin film is configured to obtain a desired infrared reflection performance.
[0166] The liquid crystal film may be a film in which any number of cholesteric liquid crystal layers that reflect light of any wavelength are laminated together, and such a liquid crystal film is configured to provide a desired infrared reflecting performance.
[0167] The infrared reflective film may contain infrared reflective particles. The infrared reflective particles are particles having infrared reflective properties, and examples thereof include flat particles having a thickness of 1 nm to 1000 μm. For example, in a resin film having silver nano-flat particles dispersed therein, an infrared reflective film having infrared reflective properties can be obtained by adjusting the thickness, surface area and arrangement of the silver nano-flat particles.
[0168] In order to have excellent infrared reflecting performance, the functional film preferably has an infrared transmittance of 40% or less at at least one wavelength within the range of 800 nm to 2000 nm. At at least one wavelength within the range of 800 nm to 2000 nm, the infrared transmittance is more preferably 30% or less, and even more preferably 20% or less.
[0169] Specifically, the transmittance of the functional film at each wavelength in the range of 800 nm to 2000 nm is measured as follows: A single functional film is prepared. Using a spectrophotometer (Hitachi High-Tech Corporation's "U-4100"), the spectral transmittance of the functional film at each wavelength in the range of 800 nm to 2000 nm is measured in accordance with JIS R3106:1998.
[0170] (Other details of interlayer film for laminated glass) The interlayer film is preferably used to obtain laminated glass without autoclaving, although it may be used to obtain laminated glass by autoclaving.
[0171] The thickness of the interlayer film is not particularly limited. From the viewpoint of practical use and of sufficiently increasing the penetration resistance and bending rigidity of the laminated glass, the thickness of the interlayer film is preferably 0.1 mm or more, more preferably 0.25 mm or more, and preferably 3 mm or less, more preferably 1.5 mm or less. When the thickness of the interlayer film is equal to or greater than the lower limit, the penetration resistance and bending rigidity of the laminated glass are further increased. When the thickness of the interlayer film is equal to or less than the upper limit, the transparency of the interlayer film and the laminated glass is further improved.
[0172] The thickness of the intermediate film is denoted by T. The thickness of each of the first layer, the first surface layer, and the second surface layer is preferably 0.005 T or more, more preferably 0.01 T or more, and even more preferably 0.02 T or more, and is preferably 0.17 T or less, more preferably 0.15 T or less, more preferably 0.13 T or less, more preferably 0.1 T or less, and even more preferably 0.09 T or less. When the thickness is equal to or more than the lower limit and equal to or less than the upper limit, the sound insulation is further improved over a wide temperature range.
[0173] The interlayer film may be an interlayer film having a uniform thickness or an interlayer film having a variable thickness. The cross-sectional shape of the interlayer film may be rectangular or wedge-shaped.
[0174] The interlayer film may be wound into a roll of the interlayer film. The roll may include a winding core and the interlayer film wound around the outer periphery of the winding core.
[0175] The distance between one end and the other end of the interlayer film is preferably 3 m or less, more preferably 2 m or less, particularly preferably 1.5 m or less, and is preferably 0.5 m or more, more preferably 0.8 m or more, particularly preferably 1 m or more. When the interlayer film has a length direction and a width direction, the distance between one end and the other end is the distance in the length direction of the interlayer film. When the interlayer film has a square planar shape, the distance between one end and the other end is the distance between the opposing ends.
[0176] The method for producing the interlayer film according to the present invention is not particularly limited. In the case of a single-layer interlayer film, the method for producing the interlayer film according to the present invention includes a method of extruding a resin composition using an extruder and a method of hot press molding. In the case of a multi-layer interlayer film, the method for producing the interlayer film according to the present invention includes, for example, a method of forming each layer using each resin composition for forming each layer, and then laminating the obtained layers, and a method of co-extruding each resin composition for forming each layer using an extruder to laminate the layers.
[0177] In view of the excellent manufacturing efficiency of the interlayer film, it is preferable that the first surface layer and the second surface layer contain the same polyvinyl acetal resin. In view of the excellent manufacturing efficiency of the interlayer film, it is more preferable that the first surface layer and the second surface layer contain the same polyvinyl acetal resin and the same plasticizer. In view of the excellent manufacturing efficiency of the interlayer film, it is even more preferable that the first surface layer and the second surface layer are formed from the same resin composition.
[0178] The intermediate film preferably has an uneven shape on at least one of both surfaces. The intermediate film more preferably has an uneven shape on both surfaces. The method for forming the uneven shape is not particularly limited, and examples thereof include a lip embossing method, an embossing roll method, a calendar roll method, and a profile extrusion method. The embossing roll method is preferred because it can form a large number of uneven embossments that are quantitatively uniform uneven patterns.
[0179] (Laminated glass) The laminated glass according to the present invention includes a first laminated glass member, a second laminated glass member, and the above-mentioned interlayer film for laminated glass. In the laminated glass according to the present invention, the above-mentioned interlayer film for laminated glass is disposed between the first laminated glass member and the second laminated glass member.
[0180] FIG. 4 is a cross-sectional view that illustrates an example of laminated glass using the interlayer film for laminated glass shown in FIG.
[0181] The laminated glass 31 shown in Fig. 4 includes a first laminated glass member 21, a second laminated glass member 22, and an interlayer film 11. The interlayer film 11 is disposed and sandwiched between the first laminated glass member 21 and the second laminated glass member 22.
[0182] A first laminated glass member 21 is laminated on a first surface 11a of the interlayer film 11. A second laminated glass member 22 is laminated on a second surface 11b of the interlayer film 11 opposite to the first surface 11a.
[0183] As described above, the laminated glass according to the present invention includes a first laminated glass component, a second laminated glass component, and an interlayer film, and the interlayer film is the interlayer film for laminated glass according to the present invention. In the laminated glass according to the present invention, the interlayer film is disposed between the first laminated glass component and the second laminated glass component.
[0184] The first laminated glass member is preferably a first glass plate, and the second laminated glass member is preferably a second glass plate.
[0185] Examples of the first and second laminated glass members include glass plates and PET (polyethylene terephthalate) films. The laminated glass includes not only a laminated glass having an intermediate film sandwiched between two glass plates, but also a laminated glass having an intermediate film sandwiched between a glass plate and a PET film or the like. The laminated glass is a laminate including glass plates, and preferably includes at least one glass plate. It is preferable that the first laminated glass member and the second laminated glass member are glass plates or PET films, respectively, and that the laminated glass includes a glass plate as at least one of the first laminated glass member and the second laminated glass member. It is particularly preferable that both the first and second laminated glass members are glass plates.
[0186] The glass plate includes inorganic glass and organic glass. The inorganic glass includes float plate glass, heat absorbing plate glass, heat reflecting plate glass, polished plate glass, patterned plate glass, lined plate glass, green glass, etc. The organic glass is a synthetic resin glass that replaces inorganic glass. The organic glass includes polycarbonate plate and poly(meth)acrylic resin plate, etc. The poly(meth)acrylic resin plate includes polymethyl(meth)acrylate plate, etc.
[0187] The thickness of each of the first laminated glass member and the second laminated glass member is preferably 1 mm or more, preferably 5 mm or less, more preferably 3 mm or less. When the laminated glass member is a glass plate, the thickness of the glass plate is preferably 0.5 mm or more, more preferably 0.7 mm or more, and preferably 5 mm or less, more preferably 3 mm or less. When the laminated glass member is a PET film, the thickness of the PET film is preferably 0.03 mm or more, and preferably 0.5 mm or less.
[0188] The manufacturing method of the laminated glass preferably includes a step of arranging an interlayer between the first laminated glass member and the second laminated glass member, and then bonding the first and second laminated glass members to the interlayer to obtain a laminate. In this step, it is preferable to remove air remaining between the first laminated glass member, the second laminated glass member, and the interlayer by passing them through a pressing roll or by placing them in a rubber bag and sucking them under reduced pressure. The temperature during bonding is, for example, 70°C to 100°C.
[0189] The interlayer film and the laminated glass can be used in automobiles, railroad vehicles, aircraft, ships, buildings, etc. The interlayer film and the laminated glass can be used for purposes other than these. The interlayer film and the laminated glass are preferably interlayer films and laminated glasses for vehicles or buildings, and more preferably interlayer films and laminated glasses for vehicles. The interlayer film and the laminated glass can be used for automobile front glass, side glass, rear glass, roof glass, etc. The interlayer film and the laminated glass are preferably used in automobiles. The interlayer film is used to obtain laminated glass for automobiles.
[0190] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0191] In the polyvinyl acetal resin used, n-butyl aldehyde with 4 carbon atoms was used for acetalization. For the polyvinyl acetal resin, the degree of acetalization (degree of butyralization), the degree of acetylation, and the content of hydroxyl groups were measured by a method conforming to JIS K6728 "Testing Method for Polyvinyl Butyral." When measured by ASTM D1396-92, the values were similar to those obtained by a method conforming to JIS K6728 "Testing Method for Polyvinyl Butyral."
[0192] The following materials were prepared:
[0193] (Polyvinyl acetal resin) Polyvinyl acetal resin (polyvinyl butyral resin (PVB1), average degree of polymerization 1700, hydroxyl group content 30.4 mol%, acetylation degree 1.0 mol%, acetalization degree (butyralization degree) 68.6 mol%) Polyvinyl acetal resin (polyvinyl butyral resin (PVB2), average degree of polymerization 850, hydroxyl group content 31.0 mol%, acetylation degree 1.0 mol%, acetalization degree (butyralization degree) 68.0 mol%) Polyvinyl acetal resin (polyvinyl butyral resin (PVB3), average degree of polymerization 1500, hydroxyl group content 30.8 mol%, acetylation degree 0.5 mol%, acetalization degree (butyralization degree) 68.7 mol%)
[0194] (Plasticizer) Triethylene glycol di-2-ethylhexanoate (3GO)
[0195] (Metal salt M) Mg mixture (a 50:50 (by weight) mixture of magnesium 2-ethylbutyrate and magnesium acetate)
[0196] (UV protection agent) Tinuvin 326 (2-(2'-hydroxy-3'-t-butyl-5-methylphenyl)-5-chlorobenzotriazole, "Tinuvin 326" manufactured by BASF)
[0197] (Antioxidants) BHT (2,6-di-t-butyl-p-cresol)
[0198] Example 1 Preparation of the composition for forming the interlayer (first layer): The following components were mixed and thoroughly kneaded with a mixing roll to obtain a composition for forming an intermediate film (first layer).
[0199] Polyvinyl butyral resin (PVB1) 37.5 parts by weight Polyvinyl butyral resin (PVB2) 62.5 parts by weight Triethylene glycol di-2-ethylhexanoate (3GO) 30 parts by weight Metal salt M (Mg mixture) in an amount of 70 ppm in the resulting interlayer film UV blocking agent (Tinuvin 326) in an amount of 0.2% by weight in the resulting interlayer film Antioxidant (BHT) in an amount of 0.2% by weight in the resulting interlayer film
[0200] Preparation of the interlayer: The composition for forming the interlayer film (first layer) was hot-press molded to produce a single-layer interlayer film (thickness 0.8 mm) including only the first layer.
[0201] (Examples 2 to 5 and Comparative Examples 1 to 4) A single-layer interlayer film (thickness: 0.8 mm) was produced in the same manner as in Example 1, except that the type and content of the resin and the content of the plasticizer were changed as shown in Tables 1 and 2.
[0202] (evaluation) (1) Glass transition temperature and softening point of the first layer The obtained first layer was stored for 12 hours under an environment of room temperature 23±2°C and humidity 25±5%. Then, the viscoelasticity was measured using a viscoelasticity measuring device "ARES-G2" manufactured by TA Instruments. Using a parallel plate with a diameter of 8 mm as a jig, the measurement was performed under the conditions of shear mode, temperature reduction from 100°C to -20°C at a temperature reduction rate of 3°C / min, frequency of 1Hz, and strain of 1%. In the obtained measurement results, the peak temperature of the loss tangent was determined as the glass transition temperature Tg (°C). The temperature at which the loss tangent value becomes minimum in the temperature range between Tg (°C) and 100°C was determined as the softening point.
[0203] (2) Weight average molecular weight and number average molecular weight of the resin contained in the first layer The first layer obtained was dissolved in N-methylpyrrolidone to prepare a 0.2 wt% solution, and the solution was filtered through a 0.45 μm filter. A sample in which lithium bromide was dissolved at a concentration of 10 mmol / ml was used as the N-methylpyrrolidone. Next, the number average molecular weight and weight average molecular weight of the polyvinyl acetal resin in terms of polystyrene were measured using a gel permeation chromatography device ("Shodex GPC-101", detector: RI-71S, autosampler: AS101, guard column: KF-G, column: LF-804, two columns in series). The measurement was performed under conditions of a flow rate of 0.5 ml / ml and a column temperature of 40°C. The following 10 samples with weight average molecular weights were used as standard samples ("Shodex Standard SM-105"). The sample numbers (weight average molecular weight) are as follows: S-1.3 (1,270), S-3.2 (3,180), S-6.9 (6,940), S-22 (21,800), S-53 (52,500), S-139 (139,000), S-333 (333,000), S-609 (609,000), S-1345 (1,350,000), and S-2704 (2,700,000). The molecular weights were plotted against the elution times of the peak tops of the respective standard sample peaks, and the resulting approximate straight lines were used as calibration curves.
[0204] (3) Compression creep test The obtained first layer (interlayer film) was cut into a diameter of 8 mm to obtain a test sample. The obtained test sample was subjected to a compression creep test by the above-mentioned method. Since the thickness of the first layer (interlayer film) was 0.8 mm, the obtained test samples correspond to test samples A, B, and C. Furthermore, the thickness of the test sample after the compression creep test was smaller than the thickness of the test sample before the compression creep test.
[0205] (4) Drop ball test (penetration resistance) Two glass plates (clear float glass) measuring 30 cm long x 30 cm wide x 2.5 mm thick were prepared. The obtained interlayer film was sandwiched between the two glass plates to obtain a laminate. The obtained laminate was placed in a rubber bag and degassed for 20 minutes at a vacuum degree of 2660 Pa (20 torr). Next, while still degassed, the laminate was heated to 90°C at a heating rate of 4°C / min, held at 90°C for 5 minutes, and then cooled to 30°C. Then, the pressure was returned to normal. In this way, a laminated glass was obtained.
[0206] An iron ball having a diameter of 82 mm and a weight of 2260 g was dropped from a height of 4 m onto the obtained laminated glass at a position 150 mm inward from the edge of the laminated glass.
[0207] [Criteria for Drop Ball Test (Penetration Resistance)] Pass: The iron ball remains held on the laminated glass after the ball drop test. Fail: After the ball drop test, the iron ball penetrates the laminated glass and falls.
[0208] (5) Foaming at the edges of laminated glass (foaming at edges) Two glass plates (clear float glass) measuring 10 cm long x 10 cm wide x 2.5 mm thick were prepared. The obtained interlayer film was sandwiched between the two glass plates to obtain a laminate. The obtained laminate was placed in a rubber bag and degassed for 20 minutes at a vacuum of 2660 Pa (20 torr). Next, while still degassed, the laminate was heated to 90°C at a heating rate of 4°C / min, held at 90°C for 5 minutes, and then cooled to 30°C. Then, the pressure was returned to normal. In this way, a laminated glass was obtained.
[0209] The obtained laminated glass was placed on a blackout curtain, and the edge of the laminated glass was visually observed and the degree of foaming was evaluated on a 5-level scale from 1 to 5. At level 1, no foaming was observed, and toward level 5, foamed areas were observed.
[0210] An example of a captured image judged to be level 1 is shown in Figure 5(a), an example of a captured image judged to be level 2 is shown in Figure 5(b), an example of a captured image judged to be level 3 is shown in Figure 5(c), an example of a captured image judged to be level 4 is shown in Figure 5(d), and an example of a captured image judged to be level 5 is shown in Figure 5(e).
[0211] (6) Transparency of laminated glass Two glass plates (clear float glass) measuring 30 cm long x 30 cm wide x 2.5 mm thick were prepared. The obtained interlayer film was sandwiched between the two glass plates to obtain a laminate. The obtained laminate was placed in a rubber bag and degassed for 20 minutes at a vacuum degree of 2660 Pa (20 torr). Next, while still degassed, the laminate was heated to 95°C at a heating rate of 6°C / min, held at 95°C for 20 minutes, and then cooled to 30°C. Then, the pressure was returned to normal. In this way, a laminated glass was obtained.
[0212] The obtained laminated glass was placed on a blackout curtain, and the transparency of the laminated glass was visually observed and rated on a 5-level scale from 1 to 5. At level 1, the entire surface was completely transparent, and toward level 5, areas with lower transparency were observed.
[0213] An example of a captured image judged to be level 1 is shown in Figure 6(a), an example of a captured image judged to be level 2 is shown in Figure 6(b), an example of a captured image judged to be level 3 is shown in Figure 6(c), an example of a captured image judged to be level 4 is shown in Figure 6(d), and an example of a captured image judged to be level 5 is shown in Figure 6(e).
[0214] The details and results are shown in the following Tables 1 and 2. Note that in the tables, the metal salt M, the ultraviolet screening agent, and the antioxidant are omitted.
[0215] [Table 1]
[0216] [Table 2] [Explanation of symbols]
[0217] 1,1B...First surface layer 2, 2B: Second surface layer 3. Middle class 3B: First middle tier 4B: The second middle tier 5B…The third middle tier 1a, 1Ba, 2a, 2Ba...First surface 11,11B…intermediate film 11A...Interlayer (first layer) 11a...First surface 11b…Second surface 21...First laminated glass member 22...Second laminated glass member 31...Laminated glass
Claims
1. An interlayer film for laminated glass having a one-layer structure or a two or more layer structure, A first layer, the first layer comprises a polyvinyl acetal resin and a plasticizer; An interlayer film for laminated glass, wherein when a test sample A having a diameter of 8 mm and a thickness of 0.8 mm obtained by cutting out the first layer is subjected to the following compression creep test, the change in thickness of the test sample A before and after the compression creep test is 50 μm or more and 325 μm or less. Compression creep test: With a load of 410 g applied to test sample A, the temperature is raised from 30° C. to 90° C. at a rate of 6° C. / min, and the sample is held at 90° C. for 5 minutes. The absolute value of the difference between the thickness of test sample A at 30° C. immediately after holding the sample at 30° C. for 5 minutes before starting the compression creep test and the thickness of test sample A immediately after holding the sample at 90° C. for 5 minutes at the end of the compression creep test is defined as the change in thickness of test sample A before and after the compression creep test.
2. The hydroxyl group content of the polyvinyl acetal resin contained in the first layer is 25 mol% or more and 38 mol% or less, 2. The interlayer film for laminated glass according to claim 1, wherein the polyvinyl acetal resin contained in the first layer has a degree of acetalization of 55 mol % or more and 75 mol % or less.
3. An intermediate film for laminated glass as described in claim 1, wherein in the first layer, the content of the plasticizer per 100 parts by weight of the polyvinyl acetal resin is 20 parts by weight or more.
4. The hydroxyl group content of the polyvinyl acetal resin contained in the first layer is 25 mol% or more and 38 mol% or less, the degree of acetalization of the polyvinyl acetal resin contained in the first layer is 55 mol % or more and 75 mol % or less; 2. The interlayer film for laminated glass according to claim 1, wherein the first layer contains 20 parts by weight or more of the plasticizer per 100 parts by weight of the polyvinyl acetal resin.
5. It has a structure of two or more layers, Further comprising a second layer, The interlayer film for laminated glass according to any one of claims 1 to 4, wherein the second layer is disposed on a first surface side of the first layer.
6. The interlayer film for laminated glass according to any one of claims 1 to 5, wherein the first layer is a surface layer in the interlayer film.
7. a first laminated glass member; a second laminated glass member; and The interlayer film for laminated glass according to any one of claims 1 to 6, The laminated glass, wherein the interlayer film for laminated glass is disposed between the first laminated glass member and the second laminated glass member.
Citation Information
Patent Citations
Intermediate film for laminated glass and laminated glass using the same
JP1998025390A
Method for manufacturing laminated glass and laminate glass
JP2009190947A
High flow polymer interlayer for laminated glass
JP2017501963A
Interlayer for laminated glass, and laminated glass
WO2016039471A1
Interlayer for laminated glass and laminated glass
WO2016158694A1